Physical training in performance bobsleigh - Costache, R. M.; Geambasu, A.; Ionel, A.; Mihalcea, A. (Science, Movement & Health, 2026)
Aim. Synergism is very important in the body's adaptation to effort respiratory cardio followed by neuro-muscular synergism and systems integrative neuro-endocrine-humoral and biochemical projection of effort. Methods. There are 4 research subjects, 2 boys and 2 girls, members of the Youth Olympic Team. Optojump is a system for analyzing the strength and resistance of the lower limbs Results. The predominant effort in the bobsled is of anaerobic lactacid type (start under 6 seconds, maximum intensity). The energy required for the mechanical work performed is ensured by the enzymatic breakdown of ATP without producing lactic acid. Conclusions. In bobbers, the motor qualities are found in a close bond of interdependence, in the following order: skill, speed, strength and endurance. Their combination characterizes the specific effort and determines the essential and decisive elements in the orientation of the preparation and the choice of means.